2021
DOI: 10.1002/anie.202105252
|View full text |Cite
|
Sign up to set email alerts
|

Materials Engineering of Violin Soundboards by Stradivari and Guarneri

Abstract: We investigated the material properties of Cremonese soundboards using a wide range of spectroscopic, microscopic, and chemical techniques. We found similar types of spruce in Cremonese soundboards as in modern instruments, but Cremonese spruces exhibit unnatural elemental compositions and oxidation patterns that suggest artificial manipulation. Combining analytical data and historical information, we may deduce the minerals being added and their potential functions—borax and metal sulfates for fungal suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…This may be one of the reasons that dicot wood appears to be more degraded than conifer wood in antique violins. [27][28][29] Between 200-1000 years of instrument aging, hemicellulose hydrolysis appears to be the most important chemical alteration. 18,30 For both antique guqin and old Italian violins, there is a common belief that their acoustic qualities improve with aging.…”
Section: The Chemistry Of Wood Agingmentioning
confidence: 99%
“…This may be one of the reasons that dicot wood appears to be more degraded than conifer wood in antique violins. [27][28][29] Between 200-1000 years of instrument aging, hemicellulose hydrolysis appears to be the most important chemical alteration. 18,30 For both antique guqin and old Italian violins, there is a common belief that their acoustic qualities improve with aging.…”
Section: The Chemistry Of Wood Agingmentioning
confidence: 99%
“…The selection of these two compounds for this study is based the fact that recent studies found high levels (1000 ppm) of Na and other elements (e.g., K, Cl, Ca, Cu and Zn etc.) residing in the cell wall structure of violins made from Stradivari and Guarneri (Taia et al, 2017;Su et al, 2021). A further assumption is that timber companies made use of salt as preservative in the waterways used to move logs, which could have, at some point, had a positive implication on the chemical structure of musical instruments (Gug, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in density by 33% in spruce boards and 10% in maple boards caused changes in the stiffness distribution, which can have a direct impact on vibration effectiveness or can indirectly change sound radiation due to the modified damping characteristics. On the other hand, Su et al 2021 [ 3 ] examined the effects of natural aging on Cremonese spruce using C13 solid-state nuclear magnetic resonance, noting that there was little sign of degradation, which was in contrast to Cremonese sycamore wood that showed significant hemicellulose degradation and the demethoxylation of lignin. Such distinctions may be caused by fundamental differences in the chemical compositions of wood.…”
Section: Introductionmentioning
confidence: 99%